Pengaruh Beberapa Tingkat Serat Kasar dalam Ransum Terhadap Pekembangan Organ Dalam Itik Jantan - Rudy Sutrisna (Politeknik Negeri Lampung., 2012)
This research was conducted to determine the effect of crude fiber level in rations of gizard weight, length and weight of small intestine, caecum, colon drake. Research using a completely randomized design consisting of four treatment levels of crude fiber (5, 10, 15, and 20%) and repeated four times. Data analysis of variance test results and continue testing the average value with Duncan Multiple Range Test. Ducks 3 weeks old experiment as much as 64 tail is divided into four treatments and each treatment consisted of four ducks. All treatments formulated rations containing protein (16%) and ME (2600 kcal/kg) is the same. The main source of crude fiber in the diet is fine bran. The results showed significantly different levels of crude fiber (P <0.05) to the length of small intestine drake. Keywords: Ducks male, Fiber, Carcas, Visceral Organ.